Outcome after surgical resection for duodenal adenocarcinoma in the UK. (16th March 2015) - Solaini, L; Jamieson, N B; Metcalfe, M; Abu Hilal, M; Soonawalla, Z; Davidson, B R; McKay, C; Kocher, H M; ,
Abstract: Background: Factors influencing long-term outcome after surgical resection for duodenal adenocarcinoma are unclear. Methods: A prospectively created database was reviewed for patients undergoing surgery for duodenal adenocarcinoma in six UK hepatopancreaticobiliary centres from 2000 to 2013. Factors influencing overall survival and disease-free survival (DFS) were identified by regression analysis. Results: Resection with curative intent was performed in 150 (84·3 per cent) of 178 patients. The postoperative morbidity rate for these patients was 40·0 per cent and the in-hospital mortality rate was 3·3 per cent. Patients who underwent resection had a better median survival than those who had a palliative surgical procedure (84 versus 8 months; P < 0·001). The 1-, 3- and 5-year overall survival rates for patients who underwent resection were 83·9, 66·7 and 51·2 per cent respectively. Median DFS was 53 months, and 1- and 3-year DFS rates were 80·8 and 56·5 per cent respectively. Multivariable analysis revealed that node status (hazard ratio 1·73, 95 per cent c.i. 1·07 to 2·79; P = 0·006) and lymphovascular invasion (hazard ratio 3·49, 1·83 to 6·64; P = 0·003) were associated with overall survival. Conclusion: Resection of duodenal adenocarcinoma in specialist centres is associated with good long-term survival. Lymphovascular invasion and nodal metastases are independent prognostic indicators. Abstract : Lymphovascular invasion and nodal status predict survival